Evaluation of Body Surface Temperature in Pigs Using Geostatistics - Maria de Fátima Araújo Alves; Héliton Pandorfi; Abelardo Antônio de Assunção Montenegro; Rodes Angelo Batista da Silva; Nicoly Farias Gomes; Taize Calvacante Santana; Gledson Luiz Pontes de Almeida; Gabriel Thales Barboza Marinho; Marcos Vinícius da Silva; Weslley Amaro da Silva (AgriEngineering, 2023)
This paper explores the potential of infrared thermography and geostatistics in animal production and presents the results of the application of the combination of these techniques, contributing significantly to efforts to obtain animals’ responses to the environments in which they are located and thereby ensuring improvements in productivity and animal welfare. The objective was to verify the variability in surface temperature in pigs submitted to different climate control systems using geostatistics. Three growing animals per stall were selected. Dry bulb temperature (Tbd, °C), relative humidity (RH, %) and thermal images were recorded at 08:00 and 12:00 h. To analyze the data, semivariograms were made, the theoretical model was validated and kriging maps were constructed. The mean temperature of the pigs in the pen with adiabatic evaporative cooling (AEC) ranged from 32.40 to 36.25 °C; for the pigs in the forced ventilation (FV) pen, the range of variation was from 32.51 to 36.81 °C. In the control group (Con), with natural ventilation, the average temperature was 37.51 to 38.45 °C. The geostatistical analysis provided a mathematical model capable of illustrating the variation in temperature in the caudal–dorsal regions of the pigs according to the environments to which the animals were subjected.